Describing macro-scale structure of the snow cover by a dynamic-stochastic model - A. N. Gelfan; V. M. Moreydo (Лëд и снег)
Possibilities to investigate the spatial structure of snow cover by means of dynamic-stochastic model are discussed in this article. Basin of the Cheboksary reservoir (area of 376 500 sq.km) was used as an example. Results of numerical experiments show that our dynamic-stochastic model of the snow cover formation reproduces a snow field structure with adequate accuracy. The fractal dimensions of the modeled fields are in good correspondence with respective dimensions of fields obtained from data of the in situ observations.